GUS BAHA’S MODERATION DISCOURSE STRATEGY ON BANK INTEREST ISSUE - Pujiyatno, Ambar; Khristianto, K; Sorayyaei Azar, Ali; Saepudin, Encep (Lire Journal, 2024)
This study aims to reveal Gus Baha’s (hereafter referred to as GB) moderation thoughts in presenting discourse on bank interest. The data sources used are the videos of GB’s Islamic lectures broadcasted by several YouTube channels. The oral text data is sorted, based on relevant theme. The data were then studied, based on Fairclough’s (1,2) discourse analysis framework, focusing on textual analysis, and its interpretation. This study applied a lexicographer tool, Ant.Cont. 3.5.9, to map the lexical choices in the speeches. Based on the analysis, the construction of the discourse is marked by the use of certain words like wong (people) for making many story telling to build a logics, the dominance of declarative structure to convey his views and reasons, the humor register to create a friendly atmosphere, and intertextuality of issue history and opinions of some big NU clerics to support his arguments. The main objective of developing a moderate and balanced discourse of bank interest is to build social control as an effort to create a conducive religious and social climate, by providing comprehensive views/arguments to accommodate the variety of opinions that arise. The function of GB’s discourse is to steer a middle way for the disputes in Muslim society